Application of systems approach to achieving cleaner and sustainable environment: A study of waste dumping issue on Idiroko Road, Ota, Ogun State, Nigeria - Daniel E. Ufua; Odunayo P. Salau; Joseph A. Dada; Mosunmola O. Adeyeye (African Governance and Development Institute (AGDI), 2020)
This research explores waste management activities and the strive to achieve a cleaner environment for man's habitation. The work applies a case study approach andthe use of observation method was applied in the data collection along with a description of the case of waste dumping issue on Idiroko Road, Ota, Ogun State, Nigeria. This study suggests the application of systems approach to enhance a participatory waste management practice, that embraces the involvement and active consultation of the concerned stakeholders for effective and sustainable waste management practice. The research also highlights the need for further research to consider the application of other data collection tools such asinterview and workshop to have a broaderdata needed to further explore the research area.
Keywords: 330; Clean environment; Environmental pollution; Systems approach; Waste management